Definition in Greek philosophy - Charles, David (David Owain Maurice) (Oxford : Oxford University Press, 2010)
David Charles presents 14 new essays by leading experts on the topic of definition in Greek philosophers from Socrates to Plotinus.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Definition (Philosophy); Philosophy, Ancient